Piłkarski Poker - Pągowski, Andrzej (1953- ). ([S.l.] : Polfilm, 1989)
Plakat filmu.
Autor za http://www.polishposter.biz/pl/p/Plakat-Pilkarski-Poker-1989/388.
Data wyd. za http://www.polishposter.biz/pl/p/Plakat-Pilkarski-Poker-1989/388.
Keywords: Plakaty filmowe -- Polska -- 1970-2000.